2014
DOI: 10.1371/journal.pone.0109039
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Exposure to di(2-ethylhexyl) Phthalate and Reproductive Hormone Levels in Fetal Blood: The Hokkaido Study on Environment and Children's Health

Abstract: Prenatal di(2-ethylhexyl) phthalate (DEHP) exposure can produce reproductive toxicity in animal models. Only limited data exist from human studies on maternal DEHP exposure and its effects on infants. We aimed to examine the associations between DEHP exposure in utero and reproductive hormone levels in cord blood. Between 2002 and 2005, 514 pregnant women agreed to participate in the Hokkaido Study Sapporo Cohort. Maternal blood samples were taken from 23–35 weeks of gestation and the concentration of the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 54 publications
3
69
1
1
Order By: Relevance
“…However, the second study reported associations between third trimester MEHP levels in maternal blood and reduced testosterone to estradiol ratios and inhibin B among males [10]. In addition, a cross-sectional study of perinatal phthalate exposure reported that MEP and MBP concentrations in breast milk were associated with increased luteinizing hormone to free testosterone ratios and SHBG in male infants at three months of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, the second study reported associations between third trimester MEHP levels in maternal blood and reduced testosterone to estradiol ratios and inhibin B among males [10]. In addition, a cross-sectional study of perinatal phthalate exposure reported that MEP and MBP concentrations in breast milk were associated with increased luteinizing hormone to free testosterone ratios and SHBG in male infants at three months of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown associations between markers of phthalate and BPA exposure and altered steroid hormone levels in adults (Ehrlich et al 2012; Meeker et al 2009; Mok-Lin et al 2010; Pan et al 2006; Sathyanarayana et al 2014; Sathyanarayana et al 2017), as well as associations between in utero or early life exposure and hormone levels in infants (Araki et al 2014; Lin et al 2011; Main et al 2006). However, few studies have investigated relationships between phthalate or BPA exposure during in utero development and subsequent hormone levels during puberty, a time at which steroid hormones play an essential role in reproductive development.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of measuring markers in the blood to determine the results of exposure to low doses of ionizing radiation has previously been demonstrated experimentally [44, 45]. Accordingly, we evaluated blood biochemistry to identify possible disruptions in general indicators (lipids, proteins, carbohydrates and electrolytes], and biomarkers of thyroid, heart, liver, kidney, brain, bone and testis (steroidogenesis) impairment.…”
Section: Discussionmentioning
confidence: 99%